2020
DOI: 10.1590/1982-3533.2020v29n1art02
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and determinants of export diversification in Brazil from 2003 to 2013

Abstract: Brazil was successful in diversifying its export package from the 1960s to the beginning of the twenty-first century. However, this performance has been more ambiguous over the last decade. This study explores the literature on the impact of export diversification on economic growth and the determinants of successful diversification. More specifically, it analyzes the dynamics of Brazilian export diversification between 2003 and 2013. The results suggest that, overall, exports momentarily concentrated in 2004,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Also, a further literature review proves the different nature of the qualitative connection and the move toward the diversification of exports to the economy, depending on the level of diversity of the exported goods, the level of development of the country's economy, and the characteristics of the resource model of the national economy and the diversification of non-oil exports. Besides, a prevailing number of scientific papers discusses the perspective of a certain indicator of international trade and diversification (Hinlo & Arranguez, 2017;Lee & Yu, 2019;Del Rosal, 2019;Mania & Rieber, 2019;De Oliveira, Jegu & Santos, 2020;Kim, 2019). Given the existing inaccuracies and controversial aspects of the methodology, within the framework of this study an attempt was made to substantiate the impact of export diversification.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, a further literature review proves the different nature of the qualitative connection and the move toward the diversification of exports to the economy, depending on the level of diversity of the exported goods, the level of development of the country's economy, and the characteristics of the resource model of the national economy and the diversification of non-oil exports. Besides, a prevailing number of scientific papers discusses the perspective of a certain indicator of international trade and diversification (Hinlo & Arranguez, 2017;Lee & Yu, 2019;Del Rosal, 2019;Mania & Rieber, 2019;De Oliveira, Jegu & Santos, 2020;Kim, 2019). Given the existing inaccuracies and controversial aspects of the methodology, within the framework of this study an attempt was made to substantiate the impact of export diversification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, the study of export diversification and its advantages over specialization has become relevant in terms of leveling the risks of fluctuations in the national economy under the impact of external shocks resulting from the portfolio effect (De Oliveira, Jegu & Santos, 2020). Thus, it is interesting to research the diversification of exports and their impact on the economies of countries with resourceoriented exports.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that interest rate stability enhances the countries' export performance. Oliveira et al (2020) analysed export diversification and its factors for Brazil's various economic regions from 2003 to 2013 by employing the generalised method of moments. Findings showed that the exports are more diversified in the Southeastern states compared to the Northeastern region, and divergence in the Centralwest region started in 2006.…”
Section: Industrial Production Remittances and Corruptionmentioning
confidence: 99%
“…It is suggested that policies aiming to take full advantage of trade agreements and reduced costs may be supportive in endorsing exports. Oliveira et al (2020) explored export divergence and its determinants for different sectors of the Brazilian economy between 2003 and 2013 by using general methods of moments. Results found that the Southeastern states and the southern region have much more diversified exports than the Northeastern states, and in the Central-West region diversification started in 2006.…”
Section: Literature Reviewmentioning
confidence: 99%